Strategi Dialektika Relasional Pasangan Suami Isteri di Masa Pandemi Covid-19 - Elisha Kristian Putri; Fanny Lesmana; Desi Yoanita (Fakultas Ilmu Komunikasi UKWMS, 2021)
This research was conducted to determine the relational dialectics strategy of married couples facing the Covid-19 pandemic. There were two couples as interviewees, the first spouse experienced work from home (WFH). The second one whose husband has worked from office (WFO). This research uses a qualitative approach with a case study method. Based on the findings of the data obtained, it shows that the WFH pair is more directed at autonomy, stability and closedness, while the WFO pair refers to connection, change and openness. From the research conducted, researchers can find five things that can cause dialectical tension for couples during a pandemic. First, the closeness of the partner depends on the age and character of the child. Second, work determines the interaction of partners during a pandemic. Third, family backgrounds shape relationships in the family. Fourth, character and personal preferences shape responses in relationships. Finally, adaptations and communication alternatives facing the pandemic. Then the strategies that are mostly used by both partners are segmentation and integration. It is also seen how communication is an important (key) in forming an agreement by adjusting between partners. Penelitian ini dilakukan untuk mengetahui strategi dialektika relasional pasangan suami isteri di masa pandemi Covid-19. Terdapat dua pasangan sebagai narasumber, pasangan pertama mengalami work from home (WFH) dan pasangan kedua yang suaminya telah work from office (WFO). Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus dan teori dialektika relasional. Berdasarkan temuan data yang diperoleh menunjukkan pasangan WFH lebih mengarah pada autonomy, stability dan closedness sedangkan pasangan WFO merujuk pada connection, change dan openness. Ditemukan lima hal yang dapat menimbulkan tegangan dialektika bagi pasangan di masa pandemi. Pertama, kedekatan pasangan dipengaruhi oleh usia dan karakter anak. Kedua, pekerjaan menentukan interaksi pasangan di masa pandemi. Ketiga, latar belakang keluarga membentuk hubungan dalam keluarga. Keempat, karakter dan preferensi pribadi membentuk respon dalam hubungan. Terakhir, adaptasi dan alternatif komunikasi dalam menghadapi masa pandemi. Mayoritas strategi yang digunakan kedua pasangan adalah segmentasi dan integrasi. Dapat disimpulkan komunikasi adalah kunci dalam membentuk kesepakatan dengan menyesuaikan diri antar pasangan.